ALPHA-MANGOSTIN POTENCY TO IMPROVE RENAL FUNCTION AND HISTOPATHOLOGICAL IMAGES IN HIGH-FAT DIET RATS - Liana, Laela Kinghua; Naufal, Gusti Azri; Tjahjani, Susy (Fakultas Kedokteran Universitas Sriwijaya, 2024)
This study aimed to study whether alpha-mangostin could protect the kidneys of high-fat diet rats using the creatinine serum level and histopathological changes as parameters. The in vivo experimental study with a completely randomized design used 30 male Sprague Dawley rats. After 7 days of adaptation, they were randomly divided into six treatment groups, each with five replications. The study was done for four weeks: NC group (given standard pellet without treatment for four weeks), five other groups were given a high-fat diet for four weeks, and at the last two weeks were added with aquadest, corn oil, alpha-mangostin dose-1, alpha-mangostin dose-2, and simvastatin, namely PTL, CO, D1, D2, and Sim group. Creatinine level was examined at the end of week 2 and week 4; the difference percentage was analyzed using ANOVA/Kruskal Wallis (α=0.05) and continued with Duncan/Mann Whitney. It was shown that creatinine level decreased in D1/D2 = PTL mice (p>0,05); kidney histopathological image in D1 was better than PTL (p<0,05). It was concluded that the alpha-mangostin kidney protection effect was not yet visible according to creatinine level, but it was visible according to histopathological image; further studies are needed.